The Effect of The Implementation of Guided Inquiry-Based Worksheet on The Empire Ability and Self-Efficacy of High School Students - Elisabeth Parwati Raharjo; Niluh Sulistyani (PRISMA, 2022)
The purpose of this research is to investigate the effect of implementing guided inquiry-based worksheets on (1) empirical abstraction ability and (2) students' self-efficacy separately. This research is a quasi-experimental research with a nonequivalent control group design type with a sample of 33 students as the experimental class and 32 students as the control class. The data were obtained through the provision of tests and the distribution of questionnaires before and after treatment. The results of the tests and questionnaires were analyzed using assumption tests (normality and homogeneity) before and after learning and hypothesis testing of the difference in the mean of the two populations. The results of the homogeneity test both before and after learning were obtained that the variance of the two classes was homogeneous, both in the questionnaire and test data. The normality test of the self-efficacy questionnaire before and after learning showed a normal distribution of data. The results of the pretest showed that both data were normally distributed, however in the posttest the data were not normally distributed. The self-efficacy data were analyzed using the t-test, while the empirical abstraction data were analyzed using the Mann-Whitney test. The results obtained in this study were (1) the use of guided inquiry-based worksheets had a significant positive effect on students' empirical abstraction abilities. (2) The use of guided inquiry worksheets also has a significant positive effect on students' self-efficacy.